Nurse staffing, direct nursing care hours and patient mortality in Taiwan: the longitudinal analysis of hospital nurse staffing and patient outcome study - Liang Yia-Wun; Chen Wen-Yi; Lee Jwo-Leun; Huang Li-Chi (BMC, 2012)
Abstract Background Studies over the past decades have shown an association between nurse staffing and patient outcomes, however, most of these studies were conducted in the West. Accordingly, the purpose of this study aimed to provide an overview of the research/evidence base which has clarified the relationship between nurse staffing and patient mortality of acute care hospital wards under a universal health insurance system and attempted to provide explanations for some of the phenomena that are unique in Taiwan. Methods Through stratified random sampling, a total of 108 wards selected from 32 hospitals in Taiwan were collected over a consecutive seven month period. The mixed effect logit model was used to explore the relationship between nurse staffing and patient mortality. Results The medians of direct-nursing-care-hour, and nurse manpower were 2.52 h, and 378 persons, respectively. The OR for death between the long direct-nursing-care-hour (> median) group and the short direct-nursing-care-hour (≦median) group was 0.393 (95% CI = [0.245, 0.617]). The OR for death between the high (> median) and the low (≦median) nurse manpower groups was 0.589 (95% CI = [0.381, 0.911]). Conclusions Findings from this study demonstrate an association of nurse staffing and patient mortality and are consistent with findings from similar studies. These findings have policy implications for strengthening the nursing profession, nurse staffing, and the hospital quality associated with nursing. Additional research is necessary to demonstrate adequate nurse staffing ratios of different wards in Taiwan.